Evaluation of punching shear strength of voided slabs considering the effect of the ratio b0/d. (1st June 2018) - Chung, Joo-Hong; Bae, Baek-Il; Choi, Hyun-Ki; Jung, Hyung-Suk; Choi, Chang-Sik
Highlights: Test results of punching shear strength of voided slabs. Numerical investigation of the punching shear strength of voided slab. Punching shear strength evaluation of voided slabs which have affected by the arrangement of voids. Newly developed control perimeter calculation method for punching shear. Abstract: Voided slabs have been used as an effective technique to replace the heavy reinforced-concrete solid slabs. In voided slabs, the punching shear strength varies according to the arrangement of voids around the column because voids intersecting a failure surface anywhere along its radial length can directly reduce the punching shear strength and voids outside a failure surface can also reduce the punching shear strength by making the variation of shear stress around its perimeter. In this study, the punching shear strength of voided slabs was evaluated according to the arrangement of voids through experimental tests and numerical simulations. As a result, the factors on influencing the punching shear strength of voided slabs were determined as the void-based reduction of the cross-sectional area at the control perimeter and the ratio of the length of the control perimeter to the effective depth of the slab. Based on these influencing factors, a new method was developed to determine that the control perimeter section produces the smallest shear strength. This method can estimate the punching shear strength of voided slab systematically by assuming the location of the control perimeter at the solid region or voided region.